2021
DOI: 10.1007/s13304-020-00918-z
|View full text |Cite
|
Sign up to set email alerts
|

Anastomosis configuration and technique following ileocaecal resection for Crohn’s disease: a multicentre study

Abstract: A limited ileocaecal resection is the most frequently performed procedure for ileocaecal CD and different anastomotic configurations and techniques have been described. This manuscript audited the different anastomotic techniques used in a national study and evaluated their influence on postoperative outcomes following ileocaecal resection for primary CD. This is a retrospective, multicentre, observational study promoted by the Italian Society of Colorectal Surgery (SICCR), including all adults undergoing elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 19 publications
3
20
0
Order By: Relevance
“…We must acknowledge this reported variation in preferred surgical approaches and outcomes [10] which could reflect lack of standardisation. The results of our study strengthen the role of video-based education and tele-mentoring to overcome the reported limited surgical trainees' exposure to these complex procedures [11]. Surgeons could share video recordings of intraoperative findings in dedicated teaching sessions of multi-institutional meetings, with the aim to enhance surgical training in IBD and facilitate standardisation of surgical techniques.…”
Section: Discussionsupporting
confidence: 63%
“…We must acknowledge this reported variation in preferred surgical approaches and outcomes [10] which could reflect lack of standardisation. The results of our study strengthen the role of video-based education and tele-mentoring to overcome the reported limited surgical trainees' exposure to these complex procedures [11]. Surgeons could share video recordings of intraoperative findings in dedicated teaching sessions of multi-institutional meetings, with the aim to enhance surgical training in IBD and facilitate standardisation of surgical techniques.…”
Section: Discussionsupporting
confidence: 63%
“…The bulk of the literature to date regarding anastomotic techniques pertains to studies of side to side anastomosis (SSA) compared to end to end anastomosis (EEA). The literature regarding these two techniques needs to be interpreted with caution as many of the studies are retrospective in nature and include a mix of both stapled and handsewn anastomoses (11,(56)(57)(58)(59)(60)(61)(62). A meta-analysis from He et al published in 2014, that included 821 patients from eight studies compared handsewn end to end anastomosis (HEEA) (n = 424) and stapled side to side anastomosis (SSSA) (n = 396) (63).…”
Section: Side To Side Anastomosis Vs End To End Anastomosismentioning
confidence: 99%
“…In two meta-analyses, one based on eight comparative studies in CD patients, and one based on seven randomized controlled trials in colorectal surgery from the Cochrane Database of Systematic Reviews, functional end-to-end anastomosis were reported with a lower leakage and overall postoperative complications rate than hand-sewn end-to-end (but not side-to-side) anastomosis. Manual or stapled end-to-end, end-to-side, and side-to-side with double blind stumps are associated with a worse long-term recurrence rate and higher postoperative complication rate [ 36 , 37 , 38 , 39 , 40 ]. There is recent evidence that anastomotic configuration probably plays a pivotal role in CD recurrence.…”
Section: Discussionmentioning
confidence: 99%